Conference between the Prime Minister and representatives of the Miners' Federation of Great Britain, 15 April 1926 (page 6)
1926-05-15 "Conference between the Prime Minister and representatives of the Miners' Federation of Great Britain, 15 April 1926 (page 6)" [g0426006.jpg], 15 April 1926, Miners' Federation of Great Britain